2018
DOI: 10.18203/2320-1770.ijrcog20180864
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal outcome in oligohydramnios: study from a tertiary care hospital, Ahmedabad, India

Abstract: Background: Most severe and frequent complication of pregnancy is Oligohydramnios and the incidence of this is observed to be about 1-5 % of total pregnancies. Objective of present study was to find the maternal and perinatal outcome, etiology associated with oligohydramnios at tertiary care hospital.Methods: This prospective study was done among 55 patients with gestational age from 30-40wks with Oligohydramnios AFI<5cms with intact membranes were analysed for perinatal outcomes admitted at department of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 12 publications
(22 reference statements)
3
12
0
Order By: Relevance
“…Similar to study done in India, in the present study no plausible causes of oligohydramnios were present in nearly half of the cases [13]. Prolonged pregnancy, hypertensive disorders of pregnancy and severe IUGR were the most common problems identi ed accounting for 37.4%, 7.3% and 6.2% respectively which is in agreement with the aforementioned study which reported similar rates.…”
Section: Sample Size Determinationsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar to study done in India, in the present study no plausible causes of oligohydramnios were present in nearly half of the cases [13]. Prolonged pregnancy, hypertensive disorders of pregnancy and severe IUGR were the most common problems identi ed accounting for 37.4%, 7.3% and 6.2% respectively which is in agreement with the aforementioned study which reported similar rates.…”
Section: Sample Size Determinationsupporting
confidence: 92%
“…Oligohydramnios poses a dilemma in management specially in set -ups with no continuous fetal monitoring [6]. Due to intrapartum complication and high rate of perinatal morbidity and mortality associated with oligohydramnios, rates of caesarean section are rising, but decision between vaginal delivery and caesarean section should be well balanced so that unnecessary maternal morbidity is prevented and perinatal morbidity and mortality are reduced [6,13].…”
Section: Determinants Of Maternal and Neonatal Outcomes Of Oligohydramentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were seen in other studies by Ahmar et al Tajinder et al Biradar et al [10]. Showed more induction in patients as compared to controls because of abnormal Doppler and/or medical/obstetric complications (like eclampsia, pre-eclampsia, GDM) and because pregnancies were not allowed to continue beyond 37 weeks in these patients.…”
Section: Discussionsupporting
confidence: 90%
“…Similar studies were done showing variable percentage of LSCS, byGolan et al 5 (35.2%), Bower Chatoor et al 6 (44%), Bansal et al 2 .,(47%).…”
Section: Resultssupporting
confidence: 72%